(3JTQjM GdajQhSGJs (3GdHfjI (B, (3BdjI GdYed (B, (3GdMeGjI (B/s - (3aGOi MLGQ (B.s ((3MdH (B:s (3TYGY ddfTQ h GdYdhe(B,s, 2003)
(3Gbhi eG jecfc GbJfGAI dage HQeLjGJ GdajQhS h JbfjGJ GdMeGjI efI(B.s
(3HQeLjGJ GdajQhS(B.s
Keywords: (3GdHQeLjGJ (B- (3ajQhSGJ(B.s